Design of model characteristics of elements on the basis of the complex biomechanical analysis of movements in acrobatic rock`n`roll - Terekhin, V.; Kruchek, E. (International Scientific Congress Slovenian Gymnastics Federation, 2017)
Formation of the athlete begins at early age. From that as the foundation of equipment of physical actions will be laid and in general the level of basic readiness is created, further achievements of engaged depend. Because of that the problem of basic preparation is considered especially actual for all the high coordinated types of sports. The main task of basic preparation is forming the technical basis, which is based on accounting to the model characteristics of Basic Element. Within the real research the possibility of design of model of Basic Element taking into account data of the complex biomechanical analysis of movements on the example of an acrobatic rock'n'roll is shown. In practice of an acrobatic rock'n'roll athletes carry out the main walkstep in the different ways. There is no uniform approach to technology of performance of this Basic Element, both for trainers and athletes. Scientific data on identification of the most rational technology of performance of the main walk-step in the acrobatic rock'n'roll is absent. To basic skills, according to the literature and opinion of the interrogated specialists, the following requirements are imposed: rationality, safety, efficiency, minimum energy consumption. However an acrobatic rock'n'roll coaches have no reference points for their realization. This fact predetermines need of designing the model of the main course on the basis of the analysis of kinematic characteristics and the intramuscular mechanism of the rationality of this basic physical action, which allows optimizing process of development of this physical action.